Prevalence of Canine Gastrointestinal Helminths and Molecular Confirmation of Toxocara canis - Syam, Sudharsi; Babu, Angalakutti Jagadeesh; Siva Swetha, Chinta; Malakondaiah, Pathipati; Suresh Bagalakote, Prashanth; Nageswara Reddy, Bashyam (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was carried out to assess the prevalence of various canine gastro-intestinal (GI) helminths in animal population and  soil in and around Tirupati city of Andhra Pradesh (India), and to confirm Toxocara canis at molecular level through Polymerase Chain  Reaction. A total of 196 faecal and 111 soil samples were collected and examined. The overall prevalence of canine GI helminths among  animal population and soil was 54.08% and 41.44%, respectively. The faecal samples were confirmed with 4 canine GI nematodes, viz., Ancylostoma spp. (20.41%), Toxocara canis (16.84%), Strongyloides stercoralis (5.61%), Trichuris vulpis (3.06%) and, one canine GI cestode,  viz., Dipylidium caninum (3.57%) and combinations of Ancylostoma spp., Toxocara canis, Strongyloides stercoralis (4.59%), while the soil  samples had Toxocara canis (19.81%), Ancylostoma spp. (14.14%), Strongyloides stercoralis (5.40%) and Trichuris vulpis (1.80%). Location  wise, the prevalence of soil transmitted canine GI helminths was the highest in public parks (46.60%) followed by veterinary dispensaries/ hospitals (44.40%), school grounds (40.00%) and temple surroundings (12.50%). The amplification of genomic DNA (extracted from adult  worms and eggs of Toxocara canis) through PCR targeting the Internal Transcribed Spacer-2 region of ribosomal DNA and subsequent  gel documentation exhibited a ~540 bp product confirming the Toxocara canis.
Keywords: Canine gastrointestinal helminths; Polymerase chain reaction; Prevalence; Toxocara canis